2007
DOI: 10.1097/hjh.0b013e3280144779
|View full text |Cite
|
Sign up to set email alerts
|

SAH gene variants are associated with obesity-related hypertension in Caucasians: the PEGASE Study

Abstract: We confirm recent evidence that the SAH locus is associated with obesity-related hypertension, in which pathophysiological context SAH variants affecting blood pressure remain, however, to be shown.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 34 publications
(35 reference statements)
1
15
0
Order By: Relevance
“…This might explain why, in our current analyses, we were able to show the association of these left ventricular phenotypes with variation in the SAH gene, whereas our earlier study was negative. 7 The PEGASE researchers 14 reported that carriers of the À1606A allele had higher blood pressure and increased body mass index compared with À1606GG homozygotes. Blood pressure and body mass index increase with advancing age.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This might explain why, in our current analyses, we were able to show the association of these left ventricular phenotypes with variation in the SAH gene, whereas our earlier study was negative. 7 The PEGASE researchers 14 reported that carriers of the À1606A allele had higher blood pressure and increased body mass index compared with À1606GG homozygotes. Blood pressure and body mass index increase with advancing age.…”
Section: Discussionmentioning
confidence: 99%
“…[22][23][24] Research into the SAH gene found its roots in studies of genes, which are overexpressed in genetically hypertensive rats. 1,25 The Suita population survey 6,26 and subsequent case-control studies 4,5,14 reported significant associations of hypertension and related phenotypes, such as obesity, hypercholesterolemia and hypertriglyceridemia, with genetic variation in the SAH gene. Telgmann et al 14 identified five polymorphisms in the SAH promoter region (CÀ1808T, GÀ1606A, À962ins/del, GÀ451A, TÀ67C), two polymorphisms in introns 5 and 7 (C+9/In5T, A+20/In7T) and one non-functional missense variant (K359N).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Possible differences in the regulation of ACSM2A and ACSM2B gene expression could be due to the additional exon present in the 5 0 UTR; this should be addressed in further gene regulatory studies. Although these results are still controversial, previously published studies emphasized the role of ACSM3 as a candidate gene in hypertension and overweight (Benjafield et al 2003;Telgmann et al 2007). Based on our findings of hepatic transcript levels in vivo, we propose that ACSM2B could be a more promising target for further studies into the role of ACSMs as disease risk genes.…”
Section: Resultsmentioning
confidence: 89%
“…ACSM3 was first described by Iwai et al as a differentially expressed transcript in the kidneys of spontaneously hypertensive rats in comparison with a normotensive rat strain (Iwai and Inagami 1991), but further investigations into its role and its polymorphisms did not produce conclusive evidence for an association with hypertension (Iwai et al 2002;Benjafield et al 2003;Telgmann et al 2007;Tikhonoff et al 2008). One or more of the other ACSM genes could account for previously observed results, since at least three more ACSM genes are located in relative proximity to ACSM3 on chromosome 16 .…”
Section: Introductionmentioning
confidence: 77%